2004
DOI: 10.1007/s00530-003-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive rate control for streaming flows over the Internet

Abstract: The existing end-to-end TCP congestion control algorithm is well suited for applications that are not sensitive to delay jitter and abrupt changes of the transmission rate, such as FTP data transfer, but it is not recommended for delivering video data, whose perceived quality is sensitive to delay jitter and changes in the sending rate. In particular, the window-based control of Reno TCP congestion control causes burstiness in data transmission, which not only requires large buffers at the client side to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the past years, the idea of applying congestion control to multimedia systems [8] has consolidated itself and it has led to several design eorts [10], [12], [14], [16].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, the idea of applying congestion control to multimedia systems [8] has consolidated itself and it has led to several design eorts [10], [12], [14], [16].…”
Section: Related Workmentioning
confidence: 99%
“…A review of these protocols along with a proposed one can be found in [10]. Among these protocols, the only congestion control for multimedia ows that has 1 On2 Truemotion VP7 codec, http://www.on2.com/ been proposed for IETF standardization is the TCP Friendly Rate Control (TFRC) [12] [14].…”
mentioning
confidence: 99%
“…The paper also shows that the Smith predictor controller with a proportional gain models the congestion control law which is employed in the today running TCP congestion control algorithm. Moreover, the model presented in Mascolo (1999) has been employed in Grieco and Mascolo (2004) to design and implement a ratebased congestion control algorithm which has been found to produce ows that are TCP-friendly. A similar plant model is employed in Quet et al (2002) to design a rate-based congestion control algorithm implemented at the router that is robust to uncertain timedelays by employing the H ∞ technique.…”
Section: Introductionmentioning
confidence: 99%